(untitled) (Altre Modernità, 2013)
In the Western tradition the term ’apocalypse’ combines the etymological meaning of both revelation and disclosure with the cataclysm foretold. The two meanings represent paradigmatic categories when referred to the Latin American continent. It is my intention to analyse how the cited values articulate and redefine in diverse contemporary representations of so many catastrophic mass disappearances: the comic strip The Eternauta (1957-59) by Hector G. Oesterheld and Francisco Solano Lopez and their sequel in 1962 (by Oesterheld alone) Anatomía humana (Human Anatomy) (1993) by Carlos Chernov and the movie A Day Without a Mexican (2004) by Sergio Arau, where traumatic events metaphorize social pressure - often bordering on violence – on specific fields. These hyperbolic view of society resorts to biblical paradigm but also highlights the changes being brought about by present-day society thus showing the historical element, always present, in the apocalyptic narratives.